Menimbang Teologi Pembebasan Islam: Refleksi Pemikiran Asghar Ali Engineer - Salim, Hs Hairus (Jurnal Orientasi Baru, 2010)
Asghar Ali Engineer (1940-…) is a distinguished scholar and activist of Islam in India. He believes in the importance of showing equal respect to all religions and he considers faith in religion as most vital for a meaningful and transformative life. A true religion should open the way to liberating movements to free people from ignorance, superstition, oppression, slavery and injustice. Faith gives dignity to freedom in thinking and acting. These are noble ideals that do not only provide inspiration to live, but also encouragement to foster creativity, purposeful and peaceful life. Somehow, Asghar Ali Engineer found that women have not been treated equally in some Muslim establishments. That is what he is struggling to change. Justice and equality is unseparable, and he believes that a true religion will not be against the struggle for justice and peace. For this reason, he develops a liberating and inter-religious theology.